Penerapan Model Pembelajaran Kooperatif Tipe Think,Talk,Write Untuk Meningkatkan Kemandirian Dan Prestasi Belajar Peserta Didik - Susanto, Hasperi; Hadiwinarto, Hadiwinarto (Yayasan Darussalam Bengkulu, 2020)
The research purpose is to describe the cooperative type learning model Think,Talk,Write to increase the students’ independence and achievement of the student learning at English subject of the first class SMA Negeri 1 Merapi Selatan Lahar Regency. The subjects of the research are the students of X IPA at the second semester of the academic year 2019/2020 SMA Negeri 1 Merapi Selatan. The research design used is classroom action research and quotient experiment. The instuments used are the tes instruments of objective questions given ti the students at every cycle.Non test instruments used are the observation sheet of teacher’s activity and the observation sheet of students’ independence. The data of test result is analized by using descriptive statistics and the data of on test result is analized by using quantitative description. From the result of this research shows that the cooperative type learning model Think,Talk and Write can increase independece and achievement of the students learning of X IPA class SMA Negeri 1 Merapi Selatan Lahat regency.